Gregory of Nazianzus on the Trinity and the knowledge of God in your light we shall see light - Beeley, Christopher A. (Oxford ; New York : Oxford University Press, 2008)
Gregory of Nazianzus receives relatively little attention from modern Western scholars, yet he is one of the most influential theologians in the history of Christian doctrine. Beeley presents a study of Gregory's doctrine of the Trinity in the full range of his theological and practical vision of the Christian life.
Introduction: Gregory's life and work -- God and the theologian -- Jesus Christ, the Son of God -- The Holy Spirit -- The Trinity -- Pastoral ministry -- Conclusion: Gregory among the fathers.
Includes bibliographical references (p. [325]-354) and index.
Description based on print version record.
Keywords: Gregory, -- of Nazianzus, Saint; Trinity; God (Christianity) -- Knowableness; RELIGION -- Christian Theology -- General; Electronic books